Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Trigonometric Formula's:
[tex]\boxed{\sf \ \sf \sin^2 \theta + \cos^2 \theta = 1}[/tex]
[tex]\boxed{ \sf tan\theta = \frac{sin\theta}{cos\theta} }[/tex]
Given to verify the following:
[tex]\bf (cos^2a) (2 + tan^2 a) = 2 - sin^2 a[/tex]
[tex]\texttt{\underline{rewrite the equation}:}[/tex]
[tex]\rightarrow \sf (cos^2a) (2 + \dfrac{sin^2 a}{cos^2 a} )[/tex]
[tex]\texttt{\underline{apply distributive method}:}[/tex]
[tex]\rightarrow \sf 2 (cos^2a) + (\dfrac{sin^2 a}{cos^2 a} ) (cos^2a)[/tex]
[tex]\texttt{\underline{simplify the following}:}[/tex]
[tex]\rightarrow \sf 2cos^2 a + sin^2 a[/tex]
[tex]\texttt{\underline{rewrite the equation}:}[/tex]
[tex]\rightarrow \sf 2(1 - sin^2a ) + sin^2 a[/tex]
[tex]\texttt{\underline{distribute inside the parenthesis}:}[/tex]
[tex]\rightarrow \sf 2 - 2sin^2a + sin^2 a[/tex]
[tex]\texttt{\underline{simplify the following}} :[/tex]
[tex]\rightarrow \sf 2 - sin^2a[/tex]
Hence, verified the trigonometric identity.
Answer:
See below ~
Step-by-step explanation:
Identities used :
⇒ cos²a = 1 - sin²a
⇒ tan²a = sin²a / cos²a
============================================================
Solving :
⇒ (cos²a) (2 + tan² a)
⇒ 2cos²a + (cos²a)(tan²a)
⇒ 2(1 - sin²a) + sin²a
⇒ 2 - 2sin²a + sin²a
⇒ 2 - sin²a [∴ Proved √]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.